Original paperBENEFICIAL EFFECTS OF JUDO TRAINING ON BONE MINERAL DENSITY OF HIGH-SCHOOL BOYS IN KOREA - Kim, P.S.; Shin, Y.H.; Noh, S.K.; Jung, H.L.; Lee, C.D.; Kang, H.Y. (Biology of Sport, 2013)
Bone mineralization is strongly stimulated by weight-bearing exercise during growth and development. Judo, an Olympic combat sport, is a well-known form of strenuous and weight-bearing physical activity. Therefore, the primary goal of this study was to determine the effects of Judo practice on the bone health of male high school students in Korea. The secondary goal of this study was to measure and compare the bone mineral density (BMD) of the hands of Judo players and sedentary control subjects. Thirty Judo players (JDP) and 30 sedentary high school boys (CON) voluntarily participated in the present study, and all of the sedentary control subjects were individually matched to the Judo players by body weight. BMD was determined by using dual-energy X-ray absorptiometry (Hologic, Bedford, MA, USA). The lumbar spine, femur and forearm BMD in the JDP group were significantly greater by 22.7%, 24.5%, and 18.3%, respectively, than those in the CON group. In addition, a significant difference in the CON group was observed between the dominant hand (DH) radius (0.710 ± 0.074 g/cm2) and the non-dominant hand (NDH) radius (0.683 ± 0.072 g/cm2), but this was not observed in the JDP group (DH = 0.819 ± 0.055 g/cm2; NDH = 810 ± 0.066 g/cm2) (P < 0.05). Therefore, the results of this study suggest that Judo practice during the growth period significantly improves bone health in high school male students. In addition, it seems that Judo practice could eliminate the effect of increased BMD in the dominant hand.